Empowerment and its impact in technical innovation Administrative An analytical study In General Company for electrical Industries - تركي, سنية كاظم (Journal of Economics and Administrative Sciences, 2017)
based search on two variables two main (Administrative empowerment ) and (technical innovation) target detection relationship and influence between the five dimensions (the delegation of authority , personnel training , effective communication, work teams , motivating employees) and (technical innovation) conducted research in General Company for electrical Industries , and through the sample included the views of managers in the various administrative levels poll .And adopted a researcher at a major tool for data collection is questionnaire designed to find, as was the contents of the questionnaire analysis according to the Statistical Information System ( Spss), The (55) to identify which research found a job related to the existence of the level of importance of research variables results came relationship between variables correlation and strong moral influence between the two variables and it was based on the formulation of.